THE PERCEPTION OF THE TEENAGERS OF PREMARITAL SEXUAL IN DENPASAR: CULTURE STUDIES PERSPECTIVE - Pradnyaparamita DuarsaI, Dyah; Ardika, Wayan; Hakimi, Mohammad; Mariyah, Emiliana (E-Journal of Cultural Studies, 2012)
The Balinese culture, mainly the community of Denpasar, is the result of along process of culture assimilation and aculturization. The modern culture whichenters Bali in some aspects includes their teenagers’ way of life and modern lifestyle. This research’s purposes: what are the teenagers’ perceptions aboutpremarital sex themselves? what are the factors that shaped the teenagers’perception?, and what is the effect and significance of the teenagers’ perception ofpremarital sex within their group in social and value systems? This research isconducted by qualitative methods with a hermeneutic and phenomenologicalapproach. The data are obtained by in-depth interview, focused group discussion(FGD) and by taking a picture with using in-depth interview, FGD andobservational guide as instruments. The informants are teenagers between 10 – 24years old in Denpasar, and the key informants are teenagers who have done sex.Teenagers are students of high school, universities as well as teens who workedand have earned. In-depth interviews are also carried out on public and religiousfigures, policy-maker in education affair, student advisors, onlooker sexualproblems as well as parents. Informants selected purposively, who have a lot ofinformation related sex among teenagers. Theories are used: The Theory ofPerception, The Theory of Hegemony, The Theory of Lifestyle and Youth Sub-Culture, and The Theory of Power and Knowledge.The result shown teenagers generally still have an ideal perception. On theother hand, there are teens who have committed premarital sex have a realityperception. The determinant factors of the perception are internal and externalfactors. The reality perception of teenagers stimulates premarital sex to becomemore widespread. The perception also influences a socio-cultural phenomenonwhich includes: cultural, social and health dimension. The perception need to beanticipated in a constructive way; that is by increasing the power of internalfactors and eliminating negative aspect of external factors.
Keywords: Perception, Teenagers, Premarital Sex